The surgical and definitive obturator after hemimaxillectomy of the palate - Yusalvi Rifai; Riezky Rhamdani; Acing Habibie Mude (Indonesian Journal of Prosthodontic, 2023)
To describe the use of surgical obturators and definitive obturators in post-hemimaxillectomy. Palatal tumour pa-tients who have undergone hemimaxillectomy surgical came to the Department of Prosthodontics for the examina-tion. Clinical examination revealed a large lesion on the left palate and involved his teeth. Two types of obturators were made, they were surgical and definitive obturators. Obturator has been used for four months and was helpful in restoring swallowing, mastication, speech, and aesthetic functions. It is concluded that the use of an obturator can help patients in swallowing, masticating, and speaking, as well as helping to restore aesthetic function.